Analysis of Environmental Literacy Profile Indonesian Students at STKIP Pesisir Selatan, West Sumatera - Arif, Muhammad; Maryani, Enok (Universitas Negeri Medan, 2023)
Environmental literacy is considered an achievement of environmental education. Preservice teachers with good environmental literacy knowledge are more likely to align their actions with their understanding. Preservice teachers have two roles: as behavioural models for their students and as members of society. This research is a descriptive study that utilizes the survey method. The subjects of this research are 50 students from the Mathematics Education, Geography Education, and Technology and Informatics Education programs at STKIP Pesisir Selatan, West Sumatera-Indonesia. The data collection instrument in this research is a questionnaire. The data analysis technique used to process knowledge data utilizes the NELA score. This research indicates that students from all three programs have moderate environmental knowledge. The environmental literacy of Geography Education students has a minor standard deviation, showing relatively low variation in the scores. On the other hand, students in the Mathematics Education and Technology and Informatics Education programs have a higher standard deviation, indicating a more significant variation in their science literacy scores. Geography Education students have higher knowledge of ecology and pollution than students from the other two programs. Meanwhile, mathematics education students have the highest scores in environmental problem-solving skills. Keywords: Analysis, Environmental Literacy, Preservice Teacher